Analisis Kepuasan Pelanggan Terhadap Kualitas Jasa Pengendalian Hama Oleh CV. Jaya Putra Mandiri Makassar - Murni, Murni (Jurnal Ekonomi Balance, 2011)
The objective of this research is "To know how effective and pest control service (Pest control) applied by Company and CV. Putra Jaya Mandiri Makassar, controlling pest completely through the application of integrated pest control (IPM) ". Population in this research is the object of research which become target to get and collect data.Jadi become Population in this research is CV. Putra Jaya Mandiri Makassar. The determination of this sample aims to express appropriately the general characteristics of the population and for investigation. The number of samples in this study were 105 people. The method of analysis used is multiple regression.After the authors describe the problems that exist, it can be concluded that the implementation of Pest Control through the application of integrated pest (IPM) is quite effective and able to eradicate pests completely and efficiently without polluting and causing health hazards on the use of chemicals.